ECOLOGICAL AUDIT AND PHYTOSOCIOLOGICAL ANALYSIS OF TROPICAL FOREST, JORAPUL, KALAMATI, JHARKHAND - P. BODRA; A. K. NAG; A. K. CHOUDHARY (The Bioscan, 2006)
The physoiognomy of Jorapul, Kalamati forest has been described. The forest is under high biotic pressure and the study reflects that some of species are on the way to disappearance. The importance value index (IVI) has been calculated for each species encountered during sampling. the study is base on species-site and site-habitat relationship and data genevated are sequential assersment of information on the basis of phytosociological analysis.